Metaphysics, intuitions and physics - Tallant, Jonathan (Wiley, 2015)
Ladyman and Ross (2007) do not think that contemporary metaphysics is in good standing. However, they do think that there is a version of metaphysics that can be made to work – provided we approach it using appropriate principles. My aim in this paper is to undermine some of their arguments against contemporary metaphysics as it is currently practiced.